REASONS FOR DISCONTINUATION OF CONTRACEPTIVE METHODS AMONG COUPLES WITH DIFFERENT FAMILY SIZE AND EDUCATIONAL STATUS - Rizvi, Farwa; Irfan, Ghazia (Journal of Ayub Medical College Abbottabad, 2012)
Background: High rates of contraceptive discontinuation for reasons other than the desire for pregnancy are a public health concern because of their association with negative reproductive health outcomes. The objective of this study was to determine reasons for discontinuation of contraceptive methods among couples with different family size and educational status. Methods: This crosssectional study was carried out at the Obstetrics/Gynaecology Out-Patient Department of Pakistan Institute of Medical Sciences, Islamabad from April-September 2012. Patients (241) were selected by consecutive sampling after informed written consent and acquiring approval of Ethical Committee. The survey interview tool was a semi-structured questionnaire. Results: Majority (68%) of women belonged to urban, and the rest were from rural areas. Mean age of these women was 29.43±5.384 year. Reasons for discontinuation of contraceptives included fear of injectable contraceptives (2.9%), contraceptive failure/pregnancy (7.46%), desire to become pregnant (63.48%), husband away at job (2.49%), health concerns/side effects (16.18%), affordability (0.83%), inconvenient to use (1.24%), acceptability (0.83%) and accessibility/lack of information (4.56%). Association of different reasons of discontinuation (chi square test) with the family size (actual number of children) was significant (p=0.019) but was not significant with husband's or wife's educational status (p=0.33 and 0.285 respectively). Conclusions: Keeping in mind the complex socioeconomic conditions in our country, Family planning programmers and stake holders need to identify women who strongly want to avoid a pregnancy and finding ways to help the couples successfully initiate and maintain appropriate contraceptive use. Keywords: Contraceptives, discontinuation, side effects